2021
DOI: 10.1111/febs.16173
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exercise in fetal development: a placental perspective

Abstract: gestational diabetes mellitus (GDM); glucose transporters (GLUTs); G protein-coupled receptor (GPCR); human chorionic gonadotropin (hCG); hypoxia inducible factor-1a (HIF-1a); luteinizing hormone/choriogonadotropin receptor (LHCGR); maternal exercise (ME); maternal obesity (MO); maximal oxygen consumption rates (VO 2 max); metastatic lymph node 64 (MLN64); superoxide dismutase 3 (SOD3); mitochondrial transcription factor A (TFAM); peroxisome proliferator-activated receptor  coactivator-1 (PGC-1); placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 166 publications
(249 reference statements)
2
26
0
Order By: Relevance
“…Given that voluntary physical activity is an essential component of EE, we separately analyzed the positive effects of a prenatal exercise intervention on neurodevelopment. More and more studies have shown that reasonable physical exercise during pregnancy is not only conducive to reducing the incidence of gestational diabetes and hypertension and the percentage of body fat in pregnant women but also conducive to promoting fetal development reflected in the increase of placental survival rate and placental hormone secretion (Hopkins et al, 2011 ; Rosa et al, 2011 ; Davies and Artal, 2019 ; Chae et al, 2021 ). Treadmill training in pregnant rats significantly increased cell proliferation, BNDF, and apoptosis inhibition protein expression in the hippocampus of adolescent and adult progeny rats (Kim et al, 2021 ), which may explain the high spatial learning ability in neonatal rat pup on the premise of voluntary exercise of maternal rats (Parnpiansil et al, 2003 ).…”
Section: The Effects Of Ee On Neurodevelopment In Brainmentioning
confidence: 99%
“…Given that voluntary physical activity is an essential component of EE, we separately analyzed the positive effects of a prenatal exercise intervention on neurodevelopment. More and more studies have shown that reasonable physical exercise during pregnancy is not only conducive to reducing the incidence of gestational diabetes and hypertension and the percentage of body fat in pregnant women but also conducive to promoting fetal development reflected in the increase of placental survival rate and placental hormone secretion (Hopkins et al, 2011 ; Rosa et al, 2011 ; Davies and Artal, 2019 ; Chae et al, 2021 ). Treadmill training in pregnant rats significantly increased cell proliferation, BNDF, and apoptosis inhibition protein expression in the hippocampus of adolescent and adult progeny rats (Kim et al, 2021 ), which may explain the high spatial learning ability in neonatal rat pup on the premise of voluntary exercise of maternal rats (Parnpiansil et al, 2003 ).…”
Section: The Effects Of Ee On Neurodevelopment In Brainmentioning
confidence: 99%
“…On the other hand, the abundance of apelin and APJ in the placenta is strongly related to placental AMPK signaling and causes the transfer of maternal glucose to the fetus because all effects in mice treated with apelin are eliminated by inactivating AMPK ( 33 , 92 ). In addition, during AMPK activation, ACC is inhibited, then the concentration of malonyl-coenzyme A (CoA) decreases, and beta-oxidation of fatty acids increases in muscle ( 15 , 93 , 94 ). In the human placenta, ACC is phosphorylated via p-AMPK to enhance fatty acid oxidation and reduce fatty acid synthesis ( 95 ).…”
Section: Possible Effects Of Apelin On Insulin Sensitivity In Pregnancymentioning
confidence: 99%
“…In obese pregnant mice, daily exercise on a treadmill reduces weight gain, lowers serum glucose and fat, and increases insulin sensitivity ( 4 , 14 ). In humans, exercising (40 to 60% of VO2max) during pregnancy reduces the risk of gestational hypertension and preeclampsia and increases energy consumption ( 15 , 16 ). The fetal and maternal cardiac response to aerobic, anaerobic, and circular exercise activities has been reported to be safe and beneficial during pregnancy in humans and animals ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations